Cathelicidin-WA Protects Against LPS-Induced Gut Damage Through Enhancing Survival and Function of Intestinal Stem Cells - Wang, Sisi; Kai, Lixia; Zhu, Luoyi; Xu, Bocheng; Chen, Nana; Valencak, Teresa G.; Wang, Yizhen; Shan, Tizhong (Frontiers in Cell and Developmental Biology, 2021)
Preservation of intestinal stem cells (ISCs) plays a critical role in initiating epithelial regeneration after intestinal injury. Cathelicidin peptides have been shown to participate in regulating intestinal damage repair. However, it is not known how exactly Cathelicidin-WA (CWA) exert its function after tissue damage. Using a gut injury model in mice involving Lipopolysaccharide (LPS), we observed that CWA administration significantly improved intestinal barrier function, preserved ISCs survival, and augmented ISCs viability within the small intestine (SI) under LPS treatment. In addition, CWA administration effectively prevented proliferation stops and promoted the growth of isolated crypts. Mechanistically, our results show that the appearance of γH2AX was accompanied by weakened expression of SETDB1, a gene that has been reported to safeguard genome stability. Notably, we found that CWA significantly rescued the decreased expression of SETDB1 and reduced ISCs death after LPS treatment. Taken together, CWA may protect against LPS-induced gut damage through enhancing ISCs survival and function via regulating genome stability. Our results suggest that CWA may become an effective therapeutic regulator to treat intestinal diseases and infections.